REKAYASA DISAIN GENERATOR OZON SEBAGAI STERILISATOR MIKROORGANISME DALAM AIR - Ferry Kriswandana; Khambali .; Erna Triastuti (JURNAL PENELITIAN KESEHATAN, 2014)
Ozone gas can be produced by a generator with mengkontakkan molecular oxygen and atomic oxygen on wave ultra violet rays. In particular the rate of ozone gas can serve as a disinfectant microorganisms in the water. The purpose of this study was to produce ozone generators as sterilisator microorganisms in the water. The study was helpful in developing techniques to process drinking water sterilisator ozonisasi through appropriate technology options for more effective and efficient . This study is  Jurnal Penelitian Kesehatan 48  a research experiment by type, where researchers are planning an ozone generator and make the treatment of the sample group, namely an input air and oxygen with different capacities for gas ozone as a disinfectant microorganisms in the water. Ozone generators are designed in the material stenless steel with a 3 inch diameter, length 2 x 100 cm with a source of electrical energy and use 40 watts of ultraviolet light 2,242 nm wavelength, the ultraviolet source inputs independent air containing oxygen and pure oxygen in order to produce ozone gas that can be used as drinking water sterilisator. In this research produced ozone levels of 0.5 ppm of ozone generator with pure oxygen mengkontakkan within 1.18 minutes (71 seconds). Ozone gas at the rate of 0.5 ppm can be sterilisator debit drinking water with large 1.2 liter/minute  Keywords: ozone generator, ozone gas, oxygen, sterilizer.